Autoimmune Encephalitis as a Differential Diagnosis of Auditory Hallucination: A Case Report - Joshi, Pranav; Sherchan, Supriya; Joshi, Pranita; Kunwar, Arun; Dhakal, Ashish (Annapurna Journal of Health Sciences, 2023)
Autoimmune encephalitis, specifically associated with anti-N-methyl-D-aspartate receptor (anti-NMDAR) antibodies, presents with a range of neuropsychiatric symptoms including personality changes, cognitive decline, memory loss, and perceptual disturbances. While the condition is more commonly observed in adults and associated with paraneoplastic conditions, its diagnosis can be challenging in the pediatric population due to a lack of strong associations with specific antibodies and cancer. This case report presents the clinical manifestation, diagnosis, and management of a 14-year-old boy with autoimmune encephalitis presenting with excessive thoughts, forgetfulness, and auditory hallucinations.